The Portraiture of Edvard Munch (Peter Watkins, 1973). Issue 3 (1st January 2014) - Peacock, Steven
Abstract: This article presents a discourse on the relationship between Edvard Munch's painting and Peter Watkins' film-making practice. It does so through a close critical analysis of Watkins' still under-celebrated 1973 tele-film Edvard Munch . The tele-film provides rich insights into the connections between the practice and aesthetic experience of painting, and that of filmed material. Feathering media and aesthetic categories, the piece also makes use of original interview content with Peter Watkins.